Character Education Values in the Traditional Government System of Pulau Tengah Society, Kerinci: Between Local and Islamic Traditions - Ahmad Jamin (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2017)
This study aimed to describe the traditional goverment system which prevailed in the society of Pulau Tengah, Danau Kerinci district, Kerinci regency, Jambi Province, especially aimed to identify the character education values in the govermental system. The method used in this study was a qualitative method with an ethnography approach. The data were obtained from the observation, interview, and documents. The participants were the customary leaders, village government leaders, religious leaders, and community leaders. Data were analyzed through looking at (1) domain analysis, (2) taxonomy analysis, and (3) cultural theme analysis. The results of the study found that there were some character education values in the traditional goverment system of Pulau Tengah society based on the customary law of basendi syarak, syarak basendi Kitabullah. The character education values found were honest, responsibility, trust, determined (istiqamah), fair and deliberation which are reflected in three salient themes that emerged in this research, namely, election, appointment and inauguration, and challenges or prohibitions for officers.